Spheroidizing annealing of thermomechanically hot-rolled steel rods: influence of the prior microstructure on the mechanical characteristic and phase transformations. (9th August 2022) - Rivolta, B.; Gerosa, R.; Panzeri, D.; Piazza, L.; Angelini, L.; Alfonso, M.; Bolognani, N.; Panzeri, A.; Parimbelli, A.; Sala, C.
ABSTRACT: Spheroidizing annealing is commonly carried out to increase the deformation capability of hot rolled steels. In this work, the influence of heat treatments at 690°C and 720°C was studied on a low-carbon boron steel. The aim of this work is to relate the mechanical characteristics of the as-spheroidized steel with the as rolled prior microstructures and spheroidizing parameters. The paper suggests a tool for selecting the best combination of the as rolled microstructure and spheroidizing parameters (temperature and time) to obtain the requested deformability. Microstructure and mechanical characteristics were studied varying the spheroidizing soaking time. Different prior microstructural conditions were obtained modifying the thermo-mechanical rolling and the Stelmor cooling parameters. Other microstructural conditions were prepared by laboratory heat treatments. The results remarked the importance of the prior microstructure on the shape and the distribution of the carbides after spheroidizing. Moreover, also the spheroidization rate was influenced by the prior microstructure.